The experiences of First Nations peoples presented in Australian Bushfire research: A scoping review protocol ... - Kabir, Humayun; Fatema, Syadani Riyad; Usher, Kim; Saunders, Vicki (OSF Registries, 2023)
Introduction/Background In recent years, the bushfire incidents have been increased globally (Walters, 2023; Fletcher et al., 2021). The recent Australian Black Summer bushfires (2019-20), the 2020 and 2018 Californian wildfires, the 2019 Amazon wildfires, and the 2017 British Columbia wildfires identify the frequency of big bushfires in the world (Fletcher et al., 2021; Kirchmeier-Young et al., 2019; National Interagency Fire Center, 2018; Barlow et al., 2020; State of California, 2020; Kramer et al., 2019). More than 600 deaths, about 50,000 housing collapses/destruction, and a total economic cost of more than US$1 trillion resulted from those bushfires (Kirchmeier-Young et al., 2019; Read et al., 2020; Bowman et al., 2020). While climate change (with special reference to the increase in greenhouse gas emissions which eventually exacerbates global warming including sea temperatures that act as fire accelerates) was identified as the main reason for the increase in bushfires (Center for Climate and Energy ...